Effect of Lactational Exposure to an Aqueous Extract of Hibiscus sabdariffa on Body Mass Index at Onset of Puberty in Female Sprague - Dawley Rats - Iyare, E.E.; Adegoke, O.A. (Pakistan Journal of Nutrition, 2011)
The present study aimed to investigate whether or not maternal consumption of aqueous extract of Hibiscus sabdariffa (HS) during lactation has any effect on the body weight and body mass index at onset of puberty in the female offspring. Eighteen in-bred virgin female Sprague-Dawley rats aged between 10-12 weeks and weighing 125±5.5g (mean±SEM) with two consecutive regular 4-day estrus cycle were used for this study. On the day of delivery, the dams and their pups were randomly assigned to one of three groups of 6 rats/group. One group had tap water (control), another had 0.6g-HSextract/100ml in their drinking water while the third group had 1.8g-HSextract/100ml in their drinking throughout lactation. Results showed that maternal consumption of aqueous extract of HS during lactation at the doses tested, delayed onset of puberty and elevated body weight and body mass index at onset of puberty in female offspring.